2008
DOI: 10.1111/j.1751-7133.2008.08344.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease in Patients With Chronic Renal Impairment: Role of Natriuretic Peptides

Abstract: Although there is overwhelming evidence that natriuretic peptides might be helpful in the diagnosis and management of congestive heart failure patients, the relationship among brain natriuretic peptides (BNP), renal function, and the severity of heart failure is less clear. It is obvious that the metabolism and elimination of BNP and N‐terminal prohormone brain natriuretic peptide (NT‐proBNP) are different with BNP clearance less dependent upon renal function. This paper reviews current data about the diagnost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…The strong effect of renal dysfunction on NT -proBNP levels contributes to the decreased sensitivity and specificity questionable. 18,19 We observed kidney dysfunction (defined as estimated glomerular filtration rate <60 ml/min/1.73 m 2 ) in 36% of the patients in our study. The serum NT -proBNP concentration is profoundly affected by renal dysfunction…”
Section: Discussionmentioning
confidence: 56%
“…The strong effect of renal dysfunction on NT -proBNP levels contributes to the decreased sensitivity and specificity questionable. 18,19 We observed kidney dysfunction (defined as estimated glomerular filtration rate <60 ml/min/1.73 m 2 ) in 36% of the patients in our study. The serum NT -proBNP concentration is profoundly affected by renal dysfunction…”
Section: Discussionmentioning
confidence: 56%
“…To mediate its action, BNP is metabolized by specific natriuretic peptide receptors found in kidney, lung, liver, and along the vascular endothelium, while the NT BNP is mainly cleared by the kidneys. 12 In a recent review, Vanderheyden et al 13 observed that, despite the potential usefulness of both BNP and Nt-proBNP in diagnosis and management of patients with heart failure, including monitoring of response to drugs and a considerable body of literature exploring the usefulness of these biomarkers relative to these assessments, optimal strategies for their application in the clinical context remain undefined. Outcomes of other studies 17,18 however, suggested to Tagore et al 19 that the relationship between renal function and BNP levels may be most strongly dependent on cardiac and volume-related factors.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the prognostic potential of plasma BNP concentrations has been investigated in several studies on patients with CKD and patients on hemodialysis and peritoneal dialysis (15,16 ). However, the diagnostic accuracy of plasma BNP and NT-proBNP concentrations for HF has been reported to be reduced in this setting (17 ). It is not yet clear whether, in HF patients with CKD and ESRD, increased plasma BNP concentrations might be due to more hemodynamic stimuli or might result from other factors such as anemia, obesity and cachexia, or impaired renal clearance of natriuretic peptide, despite similar hemodynamic stimuli.…”
Section: © 2009 American Association For Clinical Chemistrymentioning
confidence: 99%